2018
DOI: 10.1002/jcp.26282
|View full text |Cite
|
Sign up to set email alerts
|

Muscle regeneration potential and satellite cell activation profile during recovery following hindlimb immobilization in mice

Abstract: Reduced muscle activity leads to muscle atrophy and function loss in patients and animal models. Satellite cells (SCs) are postnatal muscle stem cells that play a pivotal role in skeletal muscle regeneration following injury. The regenerative potential, satellite cell numbers, and markers during recovery following immobilization of the hindlimb for 7 days were explored. In mice exposed to 7 days of hindlimb immobilization, in those exposed to recovery (7 days, splint removal), and in contralateral control musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 42 publications
(96 reference statements)
7
51
1
Order By: Relevance
“…Hindlimb suspension and fasting treatments impair satellite cell proliferation [77,78]. Immobilization decreases the number of satellite cells, whereas it increases the markers of satellite cell activation [79]. Satellite cells play little or no role in muscle hypertrophy induced by myostatin deficiency [80].…”
Section: Discussionmentioning
confidence: 99%
“…Hindlimb suspension and fasting treatments impair satellite cell proliferation [77,78]. Immobilization decreases the number of satellite cells, whereas it increases the markers of satellite cell activation [79]. Satellite cells play little or no role in muscle hypertrophy induced by myostatin deficiency [80].…”
Section: Discussionmentioning
confidence: 99%
“…Disuse muscle atrophy is an important condition that is the result of progression of other chronic and acute diseases, such as cardiac and respiratory disorders; cancer; prolonged bed rest; and critical illness. Reduced physical activity leading to deconditioning is characterized by the loss of muscle mass and function in the affected muscles in patients [ 1 , 2 , 3 , 4 , 5 ] and in animal models [ 6 , 7 , 8 ]. Muscle atrophy resulting from deconditioning may also worsen disease prognosis in patients with chronic and acute diseases regardless of the underlying condition [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several pathophysiological and biological mechanisms are involved in the loss of muscle mass and function characteristic of muscle atrophy. In this regard, a great many studies have previously demonstrated that markers of oxidative stress, inflammation, proteolysis, apoptosis, autophagy, and atrophy signaling pathways were upregulated in the atrophying muscles following periods of disuse in patients [ 11 , 12 ] and animal models [ 6 , 7 , 8 ]. Whether regenerative potential is altered in models of disuse muscle atrophy remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro findings also demonstrate that alcohol suppresses myoblast fusion under differentiation conditions [23,24,39,40]. In mice, MyoD mRNA was significantly increased after seven days of immobilization and went back to control levels by seven days of post-immobilization recovery [41]. In the present study, MyoD was decreased with alcohol at three days compared to pair-fed animals and increased after 14 days of post-immobilization recovery, suggesting that alcohol may delay a normal early increase in MyoD expression or may prolong the regeneration process such that expression in the immobilized hind limb was much higher than for pair-fed animals at two weeks post-immobilization.…”
Section: Discussionmentioning
confidence: 69%